RECENT ADVANCEMENT IN THE MANAGEMENT OF PNEUMONIA (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
Pneumonia is an infection in your lungs caused by bacteria, viruses or fungi. Pneumonia causes your lung tissue to swell (inflammation) and can cause fluid or pus in your lungs. Bacterial pneumonia is usually more severe than viral pneumonia, which often resolves on its own. Pneumonia can affect one or both lungs. Pneumonia in both of your lungs is called bilateral or double pneumonia.